2007
DOI: 10.1021/ac061774m
|View full text |Cite
|
Sign up to set email alerts
|

Gold Surface Functionalization and Patterning for Specific Immobilization of Olfactory Receptors Carried by Nanosomes

Abstract: There is substantial interest in engineering solid supports to achieve functional immobilization of membrane receptors both for investigation of their biological function and for the development of novel biosensors. Three simple and practical strategies for immobilization of a human olfactory receptor carried by nanosomes are presented. The basis of the functionalization of solid gold surfaces is a self-assembled monolayer (SAM) containing biotinyl groups. Biotinyl groups are subsequently used to attach neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 33 publications
(78 reference statements)
0
54
0
Order By: Relevance
“…They can be obtained by cell disruption, purification of membrane microsomes and then by size homogenization and miniaturization of microsomes by extensive sonication (Vidic et al, 2006;Casuso et al, 2008). Each of this nanometric vesicular structure was shown to contain one or few receptors of the given type (Casuso et al, 2008;Vidic et al, 2007). The maintenance of nanosome homogeneity in the solution suggested that they can be used as a recognition part in an elementary nanobioelectronic sensor (Casuso et al, 2008;Vidic et al, 2006;Gabriel et al, 2006).…”
Section: Spot-nosed Prototype Of Olfactory Nanobiosensormentioning
confidence: 99%
See 2 more Smart Citations
“…They can be obtained by cell disruption, purification of membrane microsomes and then by size homogenization and miniaturization of microsomes by extensive sonication (Vidic et al, 2006;Casuso et al, 2008). Each of this nanometric vesicular structure was shown to contain one or few receptors of the given type (Casuso et al, 2008;Vidic et al, 2007). The maintenance of nanosome homogeneity in the solution suggested that they can be used as a recognition part in an elementary nanobioelectronic sensor (Casuso et al, 2008;Vidic et al, 2006;Gabriel et al, 2006).…”
Section: Spot-nosed Prototype Of Olfactory Nanobiosensormentioning
confidence: 99%
“…In order to optimize nanosome functional immobilization on them, several immobilization methods were checked on miliand micrometric scale. Functional responses were observed when nanosomes were simply adsorbed on the hydrophobic surface (Hou et al, 2006;Vidic et al, 2006;Benilova et al, 2008;Vidic et al, 2007) or when the receptor was captured by its specific antibody previously grafted to the sensor surface (Hou et al, 2006;Benilova et al, 2008). To further determinate optimal surface orientation of the receptor, various tagged OR17-40 were produced in yeast.…”
Section: Spot-nosed Prototype Of Olfactory Nanobiosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane proteins are clearly observed [4]. C -Electron microscopy of an immunogold-labeled nanosome : gold grains indicate the presence of the receptor [5].…”
Section: A B C Figurementioning
confidence: 99%
“…Figure 5 : Specific immobilization of nanosomes on gold surface functionalized by a mixed Self Assembled Monolayer [6]. Schematic view of the two modes of nanosomes immobilization: nonspecific "adsorption" onto SAM, and "capture" by grafting via a specific antibody [5].…”
Section: Surface Functionalization and Functional Testsmentioning
confidence: 99%